The Never End - Reed, John. author. aut Link
XI, 188 p. 44 illus.
Keywords: “Free the piggies!” —The New York Press “Reed has captured the state of the farm today.” —The Fort Myers News-Press “A dizzying feat of writing and scholarship.” —Lynne Tillman “One plays this terrifying guessing game of animal a clef: which animal am I? Which animal is my neighbor?” —Jonathan Ames This book is the first and definitive reassessment of George Orwell, twenty-first century, written by an author at the nexus of Orwell's controversial literary, political and historical legacies. In The Never End, rabble-rouser, dogged investigator, and consummate literary stylist John Reed collects two decades of subject-Orwell findings published in Pank, Guernica, Literary Hub, The Brooklyn Rail, The Rumpus, The New York Press, The Believer, Harper’s Magazine and The Paris Review. Reed’s treatment of Orwell is corrective and peerlessly contemporary; he views Orwell in a twenty-first century global context, considering Orwell’s collaboration with Cold War intelligence operations—US and UK—with unfaltering objectivity. It’s hard to imagine that Orwell—in our own moment of global doublethink—wouldn’t have wanted his devotion to contrariety applied to the literary legacy he left behind. Animal Farm, based on a previously unknown Russian short story? Animal Farm, deployed by the CIA, MI6 and the Congress for Cultural Freedom? Orwell, turning over blacklists in a McCarthy-esque act of betrayal? The Cold War? Does it last forever? Russia, the “Axis of Evil,” and now China? But. Orwell. Course syllabi. Literary laurels. Snitch. Why do we keep coming back? For the wrong reasons? Or because we know Old Benjamin would want us to know the truth? John Reed, associate professor and the current director of the MFA in Creative Writing at The NewSchool University, is the author of numerous works, including Snowball's Chance, the unauthorized companion to Animal Farm. He’s contributed to, among other venues: Slate, The Paris Review, The Times Literary Supplement, The Wall Street Journal, Vice, Rolling Stone, The New York Times, and Harper’s Magazine. He holds an MFA in Creative Writing from Columbia University.